Effects of Wheat Flour and Baking Temperature on the Quality of Iranian Flat Bread-Part II: Thermophysical Properties - OMID, M.; AKRAM, A.; GOLMOHAMMADI, A.; KERAMAT JAHROMI, M. (Asian Journal of Chemistry, 2010)
In this sequel, trends of temperature variations at the top, middle and bottom of bread made of three commercial wheat flour cultivars (Pishtaz, Marvdasht and Chamran) are presented and discussed. Main factors of wheat flour cultivars at three different backing temperatures (232, 249 and 260 °C) and 10 backing times are considered in this research. Results show that the effects of wheat variety, baking temperature and backing time are significant at 1 %. The interactions of baking temperature on backing time are significant at 1 % for the measured dependent factors at the top and inside of bread while it is significant at 5 % for the bread bottom temperature. However, the interaction effects of variety on baking temperature, variety on backing time and also triple interaction of variety, baking temperature and baking time factors aren't significant. Results of regression analysis showed that the trend of temperature variations follow a third degrees equation.